Extended Baker map using Scan patterns for image encryption - Hung, Pham Anh; Sooraksa, Pitikhate; Klomkarn, Kitdakorn (My University, 2013)
In this paper, an improvement on free-size image encryption scheme using Baker map combining Scan patterns is proposed. The generalized discrete chaotic Baker map uses sequences of parameters generated by chaotic Gauss map to divide image matrix into boxes. Scrambling method is done by using Scan patterns in each boxes of chaotic Baker map. After scrambling method, chaotic 3-D Chen system is selected to do the pixel transformation. Through the experiments, the security of proposed scheme is tested by introducing keys analysis, entropy analysis, statistical analysis, and processing time so that the scheme achieves high encryption efficiency © 2013 IEEE.
Keywords: Baker map; Chaotic system; Chen system; Gauss map; Image Encryption; Scan patterns